Agents of change : managing the introduction of automated tools - Bouldin, Barbara M. (Yourdon P. Englewood CliffsUS, 1989)
Presents a comprehensive survey on the under-utilization of technology transfer. Provides a guide to managing change and peoples' resistance to these technological innovations.